New Remains of Megathericulus patagonicus Ameghino, 1904 (Xenarthra, Tardigrada) from the Serravallian (Middle Miocene) of Bolivia; Chronological and Biogeographical Implications - Brandoni, Diego (2017)
In this contribution, we describe new remains (skull and humeri) of the Megatheriinae Megathericulus patagonicus Ameghino, 1904, recovered from the middle Miocene fossiliferous locality of Quebrada Honda, Bolivia. We also discuss the taxonomic, biogeographical, and chronological relevance of this discovery. Referral of the new specimens described here to Megathericulus patagonicus is based on metric and morphological similarities with the holotype and a humerus that has been referred to this species. Shared features include: 1) molariforms that are mesiodistally compressed and rectangular in outline; 2) a relatively less compressed M1 with labial and lingual margins that converge slightly mesially; 3) a very long premolariform portion of the maxillae (rostrum); 4) anteriorly divergent lateral edges of the maxillae; 5) a prominent, median V-shaped notch (apex posterior) between the articular surfaces of the maxillae and premaxillae; and 6) a long, gracile humerus with a prominent anterolaterally positioned deltopectoral crest on the anterior surface and a clearly evident lateral musculo-spiral channel. Precise geographic and stratigraphic data exist for the described remains, which are closely associated with a tuff dated at 12.2–12.5 Ma (Serravallian, middle Miocene), making it the first accurately dated specimen referred to Megathericulus Ameghino, 1904.